If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -5x = 67 Solving 7 + -5x = 67 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -5x = 67 + -7 Combine like terms: 7 + -7 = 0 0 + -5x = 67 + -7 -5x = 67 + -7 Combine like terms: 67 + -7 = 60 -5x = 60 Divide each side by '-5'. x = -12 Simplifying x = -12
| -10+x+4=7x-10 | | b+11=2b | | 3a+7=4a | | 3n^2=-24-17n | | 25-.8= | | -10x+90=-x | | 3(1+2y)=y+2y+4y | | -1y=-12 | | 3a+11=a+15 | | -7y+10=45 | | 12(6t^2-t-2)=0 | | 43*120+43*-20= | | 2y+8=-12 | | -8x+83=85 | | 7n=57 | | 2x+1=23x-1 | | -150+270+30= | | 10y=-70 | | 7x^2=-15+26x | | 3b+5=b+11 | | 6x^2-36x+96=0 | | 7y=84 | | 3b+5=3b+11 | | 80=w+w+w+5+w+5 | | X+2=-29+15 | | 1-y=-7 | | -3-y=-4 | | -12y+2=-82 | | 4d^2+8d+3=3 | | -2-y=-11 | | 9x+5y= -66 | | 4x-6.2x+8=0 |